Conversión alimenticia en Cuyes pintados en la etapa de crecimiento con una Tercera Progenie de cruce Genético de Tipo Absorbente - Sangoquiza Quinga, Freddy Armando (2018)
In the present investigation, the determination of the feed conversion and the weight gain in guinea pigs painted in the growth stage with a third progeny of genetic crossbreeding of absorbent type in the Experimental and Salary Production Center (CEYSA) was carried out, by means of the control of productive parameters evidencing the genetic improvement. With the purpose of establishing the consumption of guinea pigs painted in a third progeny by using records supported by the selection parameters to verify the quality of food, determining the weight gain of guinea pigs painted in the third progeny in the growth stage . First, we proceeded to select the guinea pigs that are in their growth stage and meet the best phenotypic characteristics and are classified by their coat color: White, Black, Bay, Painted, Colorados grouping. Then we proceeded to identify them with metal earrings with their respective numbering, obtaining 11 guinea pigs 8 females and 3 males which were placed in different pools 7 A and 8 A to carry the respective record. At the end of the present investigation the following results were compiled: the guinea pig that obtained the lowest weight gain is the female of 93 earring with a weight of 209 g and the one that gained the most was the female of 82 earring with a weight gain of 507 g, the animal with the lowest feed intake is the female of arete 77 with a consumption of 757g and with higher feed consumption the Macho 93 with 1946g and the animal with the lowest feed conversion was the 77th male with 757g and the one with the highest feed conversion. Female 93 with 9.31; which pointed out that with proper feeding, proper management of the house and meeting all the parameters and needs in the stage of growth in guinea pigs can be achieved optimal food conversions to less food waste and with an optimal weight gain.